Cultural Accountability and Financial Practices in Mosque Institutions: Comparative Perspectives from Indonesia and Brunei Darussalam - Suarni, Agusdiwana; Norman Bin Hamdan; Nathasa Mazna Binti Ramli; Asharaf Bin Mohd Ramli (Universitas Muhammadiyah Makassar, 2026)
This study examines the interplay between cultural accountability and financial practices in mosque institutions through a comparative analysis of Indonesia and Brunei Darussalam. Adopting a qualitative comparative design, data were collected through semi-structured interviews, document analysis, and field observations across selected mosques representing diverse governance structures in both countries. The study conceptualizes cultural accountability as a set of embedded norms, values, and relational mechanisms—such as trust, participation, and moral responsibility—that shape financial behavior within religious institutions. The findings reveal two distinct yet complementary governance models. In Indonesia, mosque accountability is predominantly community-driven, characterized by participatory decision-making, social trust, and flexible financial practices, including welfare distribution and mosque-based economic empowerment initiatives. In contrast, Brunei Darussalam demonstrates an institutionalized model of accountability, where financial practices are regulated within a centralized state framework emphasizing compliance, standardization, and infrastructure-oriented fund allocation. Despite these differences, both contexts share a commitment to ethical stewardship, transparency, and the integration of digital financial tools to enhance accountability. This study contributes to the literature by integrating cultural and institutional perspectives into Islamic non-profit governance and highlighting the coexistence of horizontal and vertical accountability mechanisms. The findings offer practical implications for policymakers and mosque administrators in designing balanced governance frameworks that promote transparency, financial sustainability, and community welfare in Islamic institutions.